Analysis of Receptionist Service Quality to Increase Guest Satisfaction at Hotel Yusro Jombang - Safitri, Risa Hani; Mataram, I Gusti Agung Bagus; Widana, I Putu Krisna Arta (International Journal of Green Tourism Research and Applications, 2021)
This study aimed to analyze the level of receptionist service quality in increasing guest satisfaction at Hotel Yusro Jombang, East Java. The number of samples used was 60 respondents, with a purposive sampling data collection technique. The primary data collection method for service quality variables is using a questionnaire that has been tested for its validity and reliability. The analysis technique used is Customer Satisfaction Index, Servqual, and Importance Performance Analysis, presented in a Cartesian diagram. This study indicates that there is a negative, positive and neutral gap between guest perceptions and expectations. Customers are satisfied with the services provided because the value of the positive gap is more than the negative. The quality level of receptionist service in improving guest satisfaction at Hotel Yusro Jombang has been good, because the value of customer satisfaction index (CSI) of 90.22% is in the range of 81%-100%, meaning, in general, the guest satisfaction index at Hotel Yusro Jombang is on the "very satisfied" criteria. Next, based on the result of importance-performance analysis, each indicator's position in the cartesius diagram found an indicator that is a priority to be fixed, i.e., indicator in the A quadrant and an indicator that is an achievement to be maintained indicator which is in the B quadrant. As for indicators that are considered most satisfying by guests, they are X3 indicators, X5 indicators, and X10 indicators, each of them has a score of 0.04.